Differential expression of long noncoding RNAs from dental pulp stem cells in the microenvironment of the angiogenesis. (May 2020) - Li, Xinzhu; Xu, Wenan; Wu, Jingyi; Lin, Xiaoyu; Chen, Yan; Wen, Jun; Wu, Buling
Abstract: Introduction: Angiogenesis is important in pulp-dentin formation. Among the regulatory factors, long noncoding RNA (LncRNA) is a class of functional RNA molecules that are not translated into protein and involved in regulating multiple physiological processes. The different expression of LncRNA and its target gene in dental pulp stem cells (DPSCs) were explored and may provide a theoretical basis for future regulation of dental pulp angiogenesis. Methods: In this study, we cultured DPSCs from healthy dental pulp tissues and divided them into two groups: the normal DPSCs and the DPSCs cultured in vascular induction medium. In total, 40, 173 LncRNA probes and 20, 730 protein coding mRNAs were detected through microarray, which were then verified by the quantitative reverse transcription-polymerase chain reaction (qRT-PCR) method. Results: The result of differential expressions measured in LncRNA through microarray showed that 376 LncRNAs increased significantly and 426 were downregulated among the two groups of cells. Moreover, the mRNA microarray in normal cultured DPSCs showed that 629 LncRNAs were significantly upregulated, while 529 of them were downregulated compared with the DPSCs that were cultured in vascular induction medium. Gene ontology (GO) analysis inferred the molecular function of mRNAs. Pathway analysis showed that 52 signaling pathways were involved in the differentiation process of DPSCs. qRT-PCR analysis, conducted for validation, showed results consistent with the microarray analysis. Conclusions: We found that a number of different regulators are involved in inducing vascular differentiation of DPSCs, which provides a foundation for subsequent experiments.